2022
DOI: 10.7759/cureus.24244
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure and Chronic Kidney Disease Progression: An Updated Review

Abstract: Hypertension (HTN) is common in chronic kidney disease (CKD), and it may aggravate CKD progression. The optimal blood pressure (BP) value in CKD patients is not established yet, although systolic BP ≤130 mmHg is acceptable as a target. Continuous BP monitoring is essential to detect the different variants of high BP and monitor the treatment response. Various methods of BP measurement in the clinic office and at home are currently used. One of these methods is ambulatory BP monitoring (ABPM), by which BP can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 84 publications
0
6
0
Order By: Relevance
“…It has been well documented that the prevalence number of chronic kidney disease varies considerably across the world, such as, almost a third of patients living in China (132.3 million) and India (115.1 million) [ 1 ]. A significant contributor to the CKD burden is hypertension, recognized as a leading risk factor for the development and progression of kidney disease, which was reported affect up to 90% of the population with CKD and accelerating its progression [ 2 , 3 ]. The intricate interplay between hypertension and kidney function has far-reaching implications for global health [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been well documented that the prevalence number of chronic kidney disease varies considerably across the world, such as, almost a third of patients living in China (132.3 million) and India (115.1 million) [ 1 ]. A significant contributor to the CKD burden is hypertension, recognized as a leading risk factor for the development and progression of kidney disease, which was reported affect up to 90% of the population with CKD and accelerating its progression [ 2 , 3 ]. The intricate interplay between hypertension and kidney function has far-reaching implications for global health [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Of the patients who had CKD progression, 72.2% had hypertension and there was a signi cant association of hypertension and CKD progression on univariate logistic regression analysis but this association was lost on multivariate logistic regression analysis. Studies have reported hypertension is an important risk factor for CKD development and CKD progression (51,52). The difference in study ndings could be due to similar prevalence rates of hypertension in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…Higher glucose load to the last PCT segment leads to increased oxygen consumption and energy expenditure in the outer medulla [66][67][68] and local hypoxia, which can increase kidney damage. 69 Hypoxia triggers the activation of hypoxia-inducible factors HIF1 and HIF2, 70 increasing erythropoietin secretion 71 and improving the hemoglobin level. Additionally, the moderate reduction in volume leads to a rise in hemoglobin concentration, which promotes the efficient transport of oxygen to various organs, preventing hypoxia.…”
Section: Sglt2 Inhibitors' Mechanism To Enhance Oxygen Transport and ...mentioning
confidence: 99%